2018
DOI: 10.1097/pas.0000000000001045
|View full text |Cite
|
Sign up to set email alerts
|

Intralymphatic Spread is a Rare Finding Associated With Poor Prognosis in Diffuse Large B-Cell Lymphoma With Extranodal Involvements

Abstract: Intralymphatic spread is common in solid cancers, but has been rarely studied in lymphomas. Review of 635 extranodal specimens from 475 diffuse large B-cell lymphoma (DLBCL) patients revealed intralymphatic spread in 10 surgical resection specimens from 10 patients including 9 de novo DLBCLs and 1 Richter transformation. The prevalence in de novo DLBCL with extranodal involvements was 1.65%. The most common involved site of intralymphatic spread was the gastrointestinal tract, followed by the female genital tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 30 publications
3
14
3
Order By: Relevance
“…Regarding morphology, we previously observed that intralymphatic spread is a rare finding and is associated with poor prognosis in DLBCL [6]. In extranodal organs (for example, the gastrointestinal tract, breast, and female genital tract), we observed peritumoral lymphatic vessels were distended with lymphoma cells, reminiscent of tumor emboli of solid cancers [6]. In the previous case series, we found intralymphatic spread in various histological structures, but mucosa was generally spared.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Regarding morphology, we previously observed that intralymphatic spread is a rare finding and is associated with poor prognosis in DLBCL [6]. In extranodal organs (for example, the gastrointestinal tract, breast, and female genital tract), we observed peritumoral lymphatic vessels were distended with lymphoma cells, reminiscent of tumor emboli of solid cancers [6]. In the previous case series, we found intralymphatic spread in various histological structures, but mucosa was generally spared.…”
Section: Introductionmentioning
confidence: 61%
“…Fluorescence in situ hybridization (FISH) has demonstrated that MYC rearrangement correlates with poor prognosis [5]. Regarding morphology, we previously observed that intralymphatic spread is a rare finding and is associated with poor prognosis in DLBCL [6]. In extranodal organs (for example, the gastrointestinal tract, breast, and female genital tract), we observed peritumoral lymphatic vessels were distended with lymphoma cells, reminiscent of tumor emboli of solid cancers [6].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although surprising, these results could account for specific properties of extra-nodal DLBCL which exhibit an initial confinement to a single anatomical site and less propensity to disseminate [ 42 ]. Interestingly, a recent study has shown that, in contrast to solid cancers, intra-lymphatic spread of extra-nodal DLBCL lymphoma cells was a rare event [ 43 ] which might explain the lesser propensity of these tumors to disseminate. Thus, the down-expression of STIM1 or Orai1 could impair cell migration and/or intralymphatic spread, promoting homing of tumor B cells to extra-nodal sites.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 This striking intrasinusoidal pattern in a lymph node with DLBCL is highly unusual, 5 although sinusoidal involvement at extranodal sites has been reported. 6 On imaging, lymphomas may present in a pattern resembling a widely metastatic pancreatic carcinoma, 7 making the clinical differentiation difficult. Sinusoidal involvement by lymphoma cells as illustrated by this case can be a diagnostic pitfall, particularly in this setting.…”
Section: Discussionmentioning
confidence: 99%